Determinants of brain drain in Nigeria: Does financial inclusion matter? - Ahmed Alhaji Aliyu; Mutalib Tunde Lawal (Journal of Governance and Accountability Studies, 2024)
Purpose: Nigeria has witnessed a substantial emigration of educated and skilled workers to other countries in the quest for greener pastures. Developing nations, such as Nigeria, with a recognizable number of highly educated and skilled individuals with an attitude to work to earn a living, are potentially exposed to brain drain syndrome, which is inimical to economic prosperity struggles. Hence, this study investigated whether financial inclusion is a determinant of brain drain in Nigeria. Method: Quantitative methods were used in this study, employing ARDL-ECM regression to analyze both short- and long-run relationships among the variables. Data were collected from the International Monetary Fund, Nigeria Bureau of Statistics, and the Central Bank of Nigeria (2003–2022). Results: The study established that Gross Domestic Product per Capita, ATMs per 100,000 Adults, Deposits with Commercial Banks % to GDP and Political Stability have a negative relationship with Brain Drain in Nigeria, whereas unemployment, bank credit to the private sector, and government efficiency have a positive relationship with brain drain. Limitations: The study was limited to Nigeria, and the findings may not be generalizable to other countries. Contributions: This study contributes to the field of finance in terms of financial inclusion matters and to the Nigerian government by identifying the determinants of brain drain in Nigeria. Novelty: This study added financial inclusion as a determinant of brain drain in Nigeria, which other existing studies have not covered.